Writing and Gender in the Royal Commentaries - Chang Rodriguez, Raquel (2017)
Comentarios reales (1st part, 1609; 2nd part, 1617) by the Cuzcan chronicler Inca Garcilaso de la Vega (1539-1616), is a key work in the literary and cultural history of America and the Hispanic world. Although the chronicle has been studied from different disciplinary perspectives, less attention has been paid to the function of gender. This essay emphasizes how Inca Garcilaso intertwined in his narration, events and deeds related to his mother, palla Chimpu Ocllo. It proposes that episodes marked by her presence contribute to shape a more nuanced reinterpretation of Peruvian history, now marked by the presence of gender.